Improving Students' Learning Activeness and Learning Outcomes through the Teams Games Tournament (TGT) Learning Model Assisted by Interactive Media in Grade IV Students at UPTD SDN Keleyan 4. - Wurrotul Kamila; Metha Putri Waluyo; Naesa Safitri; Heikmah Wijaya; Wahyu Adi Pratama; Agung Setyawan (Journal of Action Research in Education, 2026)
This study aimed to improve the science learning outcomes of fourth-grade students at UPTD SDN Keleyan 4 through the implementation of the Teams Games Tournament (TGT) learning model assisted by Canva and Quizizz. The study was motivated by low student learning outcomes, limited participation in learning activities, and the lack of variation in instructional media used during the learning process. This research employed Classroom Action Research (CAR) conducted in two cycles involving 16 fourth-grade students of UPTD SDN Keleyan 4. Data were collected through learning achievement tests, observations, and documentation. Quantitative data were analyzed using descriptive comparative techniques, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed a significant improvement in students’ learning outcomes after the implementation of the TGT model assisted by Canva and Quizizz. The average score increased from 51.81 in the pre-cycle to 84.38 in Cycle I and 89.38 in Cycle II. Furthermore, classical learning mastery improved from 0% in the pre-cycle to 81.25% in Cycle I and 87.50% in Cycle II. These findings indicate that the Teams Games Tournament (TGT) model assisted by Canva and Quizizz effectively improves science learning outcomes and enhances student engagement in the learning process.